Russia's macroeconomy—a closer look at growth, investment, and uncertainty - Torbjörn Becker (Stockholm School of Economics, Stockholm Institute of Transition Economics (SITE), 2019)
This paper looks at economic growth and its fundamental determinants in Russia over the last decades. It starts by showing that, contrary to the views of some political commentators, growth is highly important for the popularity of president Putin. Furthermore, regular models of growth are relevant to Russia and other transition countries over the last two decades and one important determinant of growth is investments in physical capital. This in turn is correlated with FDI, which is also key for Russia's strategy to modernize and diversify its economy away from oil, gas and minerals extraction. However, FDI is negatively impacted by the policy uncertainty that Russia generates both by domestic and foreign policy. Reforming institutions on paper will not be enough to reverse the trend of declining FDI but has to be accompanied by a regime that refrains from policy actions at home and abroad that add to the significant macroeconomic volatility that is already created by large swings in international oil prices.
Keywords: E60; F40; O52; 330; Russia; Putin; macroeconomics; growth; investments; FDI; volatility